Impact of Diseases on Pig Farming Enterprises in Manokwari Regency - Turot, Rofiko; Mulyadi, Mulyadi; Widodo, A.P.Edi (Fakultas Peternakan Universitas Jambi, 2026)
Background: Pig farming plays a crucial role in supporting food security, rural livelihoods, and socio-cultural traditions in West Papua, Indonesia. However, disease outbreaks have emerged as a major constraint to productivity and economic sustainability in smallholder pig production systems. Purpose: This study aimed to identify major diseases affecting pig farms in Manokwari Regency, analyse their impacts on productivity and farm income, quantify economic losses, and examine preventing the spread of diseases strategies adopted by farmers and government institutions. Methods: A quantitative descriptive approach was employed using a survey method involving 30 pig farmers selected through purposive sampling. Primary data were collected through structured questionnaires, in-depth interviews, and field observations. Data were analysed using descriptive statistics and multiple linear regression to examine the effects of morbidity and mortality on net farm income. Results: African Swine Fever, Classical Swine Fever, parasitic infections, and bacterial diarrhoea were the dominant diseases affecting pig farms. The average morbidity and mortality rates were 16.16% and 8.24%, respectively. Both morbidity and mortality had negative effects on net income, with mortality exerting a stronger economic impact. Each one percent increase in mortality reduced farmers’ net income by approximately IDR 492,600, while a one percent increase in morbidity reduced income by about IDR 272,500. Disease outbreaks also increased treatment costs and caused substantial economic losses. Conclusion: Livestock diseases significantly undermine the economic performance of smallholder pig farming in Manokwari. Strengthening biosecurity systems, improving access to veterinary services, and enhancing farmer capacity in disease prevention are essential to promote sustainable pig production.